Long-term progression of clinician-reported and gait performance outcomes in hereditary spastic paraplegias - Cubillos Arcila, Diana Maria; Dariva Machado, Gustavo; Martins, Valéria Feijó; Leotti, Vanessa Bielefeldt; Schüle, Rebecca; Peyré-Tartaruga, Leonardo Alexandre; Saute, Jonas Alex Morales (Frontiers in Neuroscience, 2023)
Introduction Hereditary spastic paraplegias (HSPs) are a heterogeneous group of neurodegenerative diseases in which little is known about the most appropriate clinical outcome assessments (COAs) to capture disease progression. The objective of this study was to prospectively determine disease progression after 4.5 years of follow-up with different clinician-reported (ClinRO) and gait performance outcomes (PerFOs). Methods Twenty-six HSP patients (15 SPG4, 5 SPG7, 4 SPG5, 2 SPG3A) participated in this single-center cohort study in which the ClinRO: Spastic Paraplegia Rating Scale; and the PerFOs: 10-meters walking test and timed-up and go (TUG), at self-selected and maximal walking speeds; Locomotor Rehabilitation Index; and 6-min walking test were performed at baseline and after 1.5 (18 patients) and 4.5 (13 patients) years. Results In the 3-year interval between the second and third assessments, significant progressions were only found in PerFOs, while in the overall 4.5 years of follow-up, both PerFOs and ClinROs presented significant progressions. The progression slopes of COAs modeled according to the disease duration allowed the estimation of the annual progression of the outcomes and sample size estimations for future clinical trials of interventions with different effect sizes. TUG at maximal walking speed was the only COA capable of differentiating subjects with a worse compared to a stable/better impression of change and would require the smallest sample size if chosen as the primary endpoint of a clinical trial. Discussion These findings indicate that both performance and clinician-reported outcomes can capture long-term progression of HSPs, with some PerFOs presenting greater sensitivity to change. The presented data are paramount for planning future disease-modifying and symptomatic therapy trials for this currently untreatable group of diseases.